Indicadores de saúde ambiental relacionados ao uso agrícola de agrotóxicos e câncer no estado de Mato Grosso - Brasil - Curvo, Hélen Rosane Meinke (2012)
The relationship between environmental pollution (environmental constraints) and human health is complex, having in common the link economic growth. The State of Mato Grosso has adopted a growth model based on modern agriculture with monocultures over large tracts of land and dependent on pesticides on a large scale, which leads to specific effects on human health. Among these effects is cancer, which sets up as the second cause of death by disease in the state. Objective: To analyze the environmental health indicators related to agricultural use of pesticides and cancer taking as reference the years 1996 to 2006. Specific Objectives: To identify indicators of environmental health, economic and characterize the process of agricultural production; identify the use of pesticiderelated morbidity and mortality from cancer, relate the agricultural use of pesticides with the indicators of cancer in the population under 20 years in municipalities in the state of Mato Grosso. Methodology: 1) Construction of integrated array of indicators of health and environment for the state of Mato Grosso through historicaldocumentary of the process of economic growth and agricultural production model, literature review of the effects of pesticides on human health and cancer 2) Ecological study analyzing temporal indicators compared records of pesticide use and indicators of morbidity and mortality from cancer in people under 20 municipalities in the state of Mato Grosso. Results: We constructed an array of indicators of environmental health for the state of Mato Grosso through historicaldocumentary of the process of economic growth and agricultural production model and effects of pesticides on human health and cancer. We identified 5.98% of municipalities in the state with the worst rates of pressure in 1996 and increased to 9.93% in 2006. With average scores were 13.68% of the municipalities in 1996 and rose to 53.90% in 2006. But the 80.34% of the districts with high results, remaining 36.17% in 2006. It can be seen worsening indicators of pressure in the comparisonbetween these years. Regarding the use of pesticides, selected indicator for Component Status, observed in 1996 only 1.71% of municipalities with worse outcomes and increased to 5.67% in 2006. The percentage of districts identified with a mean score remained between 7 and 8% in the year assessed. Within this component the percentage of municipalities with better results decreased from 90.60% in 1996 to 82.27% in 2006. In the ecological study showed that the average use of pesticides in municipal regions showed statistically significant association for both cancer mortality rates in children under 20 years (p = 0.021) and for cancer mortality of children and adolescents (p = 0.005), with 95% CI. Conclusion: The combined use of the methodology by levels of complexity showed that economic growth and processes of agricultural production - produce and reproduce different effects and risks related to cancer.